Multicultural Islamic Education and the Challenge of Majority Authoritarianism in Indonesia - Siti Handika; Inten Emilya; Ari Wibowo; Asiyah Asiyah (Peradaban Journal of Interdisciplinary Educational Research, 2026)
This study examines the role of multicultural-informed Islamic education in addressing the challenges of majority authoritarianism within plural societies, particularly in the Indonesian context. Majority authoritarianism refers to the tendency of dominant religious interpretations to shape educational narratives and institutional practices in ways that marginalize alternative perspectives and limit recognition of diversity. Employing a Systematic Literature Review (SLR) approach, this research analyzes scholarly works, policy documents, and theoretical discussions related to Islamic education, multiculturalism, and democratic values. The analysis focuses on three main themes: the manifestation of majority authoritarianism in Islamic education, the conceptual foundations of multicultural-based Islamic education, and the development of multicultural education policies in Indonesia. The findings indicate that multicultural-informed Islamic education provides a critical pedagogical framework capable of challenging exclusivist religious narratives and promoting inclusive learning environments. By integrating principles of justice, dialogue, and respect for diversity, Islamic education can function as a transformative space that cultivates democratic awareness and social responsibility. The study also highlights that although Indonesia has adopted policies promoting religious moderation and multicultural education, significant challenges remain in translating these policies into classroom practices. This article contributes theoretically by introducing majority authoritarianism as an analytical lens in Islamic education studies and practically by emphasizing the importance of strengthening multicultural-based pedagogical approaches to enhance democratic resilience in plural societies. Penelitian ini mengkaji peran pendidikan Islam berbasis multikultural dalam merespons tantangan otoritarianisme mayoritas dalam masyarakat plural, khususnya dalam konteks Indonesia. Otoritarianisme mayoritas merujuk pada kecenderungan interpretasi keagamaan dominan yang membentuk narasi pendidikan dan praktik kelembagaan sehingga memarginalkan perspektif alternatif dan membatasi pengakuan terhadap keberagaman. Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) dengan menganalisis berbagai karya ilmiah, dokumen kebijakan, dan kajian teoretis yang berkaitan dengan pendidikan Islam, multikulturalisme, dan nilai-nilai demokrasi. Analisis difokuskan pada tiga tema utama, yaitu bentuk-bentuk otoritarianisme mayoritas dalam pendidikan Islam, landasan konseptual pendidikan Islam berbasis multikultural, serta perkembangan kebijakan pendidikan multikultural di Indonesia. Hasil kajian menunjukkan bahwa pendidikan Islam berbasis multikultural menawarkan kerangka pedagogis kritis yang mampu menantang narasi keagamaan eksklusif sekaligus mendorong terciptanya lingkungan pembelajaran yang inklusif. Dengan mengintegrasikan prinsip keadilan, dialog, dan penghargaan terhadap keberagaman, pendidikan Islam dapat berfungsi sebagai ruang transformatif untuk membangun kesadaran demokratis dan tanggung jawab sosial. Penelitian ini juga menunjukkan bahwa meskipun kebijakan pendidikan di Indonesia telah mendorong moderasi beragama dan nilai-nilai multikultural, masih terdapat kesenjangan antara kerangka kebijakan dan praktik pembelajaran di tingkat institusi pendidikan. Secara teoretis, artikel ini memperkaya kajian pendidikan Islam dengan menghadirkan konsep otoritarianisme mayoritas sebagai lensa analitis, serta secara praktis menekankan pentingnya penguatan pendekatan pedagogi multikultural dalam meningkatkan ketahanan demokrasi di masyarakat plural.